Pemahaman Konseptual dalam Fisika dan Astronomi: Analisis Bibliometrik - Muhammad Reyza Arief Taqwa; Endi Suhendi; Handy Faishal Rahim (Universitas Garut, 2025)
This study presents a bibliometric analysis of research related to conceptual understanding in physics and astronomy (CUPA), analyzing publication trends, the most contributors, and emerging research directions from 2006 to 2025. The analysis was conducted on 447 documents using VOSviewer and Biblioshiny, as well as Microsoft Excel and Origin to aid data visualization. The analysis revealed a steady increase in the number of publications over time, particularly from 2017 to 2021, reflecting growing interest in this field. Collaborative efforts, both locally and internationally, are prominent, with a strong foundation in the previous literature. The main topics identified include e-learning, computer-aided instruction, and quantum optics, illustrating the influence of educational technology and advanced scientific research. Although research on CUPA has developed significantly, future studies should explore the integration of artificial intelligence (AI) in learning, investigate differences in conceptual understanding across educational systems, and address gaps in research conducted in non-English languages. This study highlights the importance of international collaboration and the need for further research to connect conceptual understanding with critical thinking and problem-solving skills, which are essential in 21st-century education.